Pengaruh Perubahan Tingkat Suku Bunga Kredit Bank Konvensional dan Tingkat Suku Bunga Bank Indonesia terhadap Pembiayaan Bank Islam berbasis Murabahah - Wicaksono, Rianto Anugerah (Universitas Brawijaya, Indonesia, 2015)
The research objective - This study aims to determine the dynamic effect of changesin interest rates of conventional bank and bank interest rates in Indonesia against thefinancing murabaha Islamic Bank. The data and methods of analysis - This study uses monthlydata from the Indonesian banking statistics from January 2009 to April 2014. The analysismethod uses the Unit Root Test, Cointegration Analysis, Impulse Response Function (IRF)and Variance Decomposition (VDC). The results of the study - the results of this study indicatethat changes in mortgage interest rates Conventional Bank has an influence on thevalue equivalent rate financing murabaha Islamic Bank, although these changes do notsignificantly affect the total amount of financing murabaha. Changes in the total amount offinancing is more influenced by movements in the interest rate set by Bank Indonesia (BIrate).